Perspective: Narrative Storyliving in Virtual Reality Design - Vallance, Michael; Towndrow, Phillip A. (Frontiers in Virtual Reality, 2022)
The development and relative affordability of virtual reality in recent years have provided opportunities to experience representations of both concrete and abstract situations; from nuclear engineering to particle physics, art galleries to three-dimensional prehistoric paintings, person-to-person communication to artificial agent collaboration, and 360-degree journalism to animated movies. Yet, it still remains challenging for participants to create personal narratives within a virtual world beyond that structured by its original designers. Setting aside technological considerations, we attribute this limitation largely to a restricted conceptualization of time and space that is fixed to present events, emotions and experiences. As a consequence, virtual reality scenarios as immersive and plausible as they might be are nonetheless prone to a thin and static view of the (virtual) world where growth and learning from experience are not always possible or privileged. In this Perspective we propose a recasting of Virtual Reality that combines novelistic storytelling in the physical world with ‘narrative storyliving’ as a mechanism for meaning-making within and across large dialogic arenas. This involves us drawing on ideas from the Russian philosopher and theorist, Mikhail Bakhtin, relating to the literary artistic chronotope. Ultimately, we intend to advance the discourse about what virtual reality is at present and where it could go as seen through a critical literary lens.